Prevention of Anemia in Adolescent Girls Through Adolescent Posyandu Activities in Bocor Village - Mutoharoh, Siti; Kusumastuti, Kusumastuti; Rahmadani, Wulan (Prosiding University Research Colloquium, 2022)
Anemia is a condition where the number of red blood cells or the concentration of oxygen carriers in the blood, namely hemoglobin [Hb] is not sufficient for the physiological needs of the body. The incidence of anemia in adolescents aged 15-24 in Indonesia based on Riskesdas in 2018 was 32%. The purpose of this community service is to increase the knowledge of young women about anemia in adolescents, including the causes, complications, methods of prevention, and management of anemia. The method of this activity is through the provision of health education to 35 young women who attend. Measurement of knowledge was carried out before and after counseling using a questionnaire. The results of the activity showed a significant increase in the level of knowledge of young women about anemia in adolescents. Before the activity, most of the youth’s level of knowledge was adequate [51%], while after the activity, most of the youth’s level of knowledge was good [54%]. The conclusion of community service activities through health counseling at the youth posyandu can increase knowledge about anemia in adolescent girls so that it is expected to be able to prevent anemia, especially in adolescent girls.